Comparative efficacy and acceptability of selective serotonin reuptake inhibitor antidepressants for binge eating disorder: A network meta-analysis - Duan, Hanying; Zhu, Lijun; Li, Min; Zhang, Xinyue; Zhang, Beilin; Fang, Shaokuan (Frontiers in Pharmacology, 2022)
Background: There are several kinds of antidepressants currently used to treat binge eating disorder (BED), but the efficacy and acceptability of these antidepressants are still controversial. Therefore, we conducted a network meta-analysis (NMA) to compare the efficacy and acceptability of different antidepressants for the treatment of BED. Methods: Five databases including PubMed, Embase, The Cochrane Library, CBM (China BioMedical Literature Service System) and CNKI (China National Knowledge Infrastructure) were systematically searched for the eligible randomized controlled trials (RCTs) for the treatment of patients with BED. The analysis was performed with Stata16 software. Results: 11 RCTs were included in this NMA. The results of the study showed that compared with placebo, sertraline and fluoxetine could significantly reduce the frequency of binge eating. Fluoxetine was ranked to be associated with the largest decrease in HAMD score. Besides, in comparison to the placebo control, none of the investigated antidepressants was associated with a significantly change in weight. In addition, all the investigated antidepressants were suggested to be well acceptable in regards to the acceptability reflected by the dropout rate. Conclusions: Fluoxetine was probably the best option when it comes to the efficacy and acceptability of antidepressants for BED.